Potential Conflicts in Pilkada in South Sumatra Province Reflection of the 2019 Simultaneous Election for 2024) - Meita Istianda (Journal La Sociale, 2023)
This research aims to find out why South Sumatra Province can avoid broad and sharp political conflicts, even though the people of South Sumatra are known for their hard character. Political conflicts in the 2019 simultaneous elections occurred in the districts of Empat Lawang, Musi Rawas, North Musi Rawas, Banyuasin, and East OKU. The potential for high conflict is rioting, as for example happened in Empat Lawang. However, even though there was a riot at the time, it only lasted for a short time, was well controlled, and caused no casualties. This is also the case with other political conflicts, so that it actually places this area as a zero conflict area. This is interesting, considering that the people in this area have a strong character. The research method used is qualitative. Data were collected through observation and in-depth interviews, and FGDs. The findings of this study show that the people of South Sumatra are people whose political culture is rational, pragmatic, patriarchal. In conclusion, the political culture is able to avoid South Sumatra from high political conflict.